2010
DOI: 10.1002/cncr.24997
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell‐free DNA in ovarian cancer

Abstract: BACKGROUND: Cell‐free DNA reflects both normal and tumor‐derived DNA released into the circulation through cellular necrosis and apoptosis. The authors sought to determine the role of preoperative total plasma cell‐free DNA levels in predicting clinical outcome in patients with ovarian cancer. METHODS: After institutional review board consent, DNA was extracted from plasma of 164 women with invasive epithelial ovarian carcinoma (EOC), 49 with benign ovarian neoplasms, and 75 age‐matched controls. The samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(64 citation statements)
references
References 25 publications
3
60
0
1
Order By: Relevance
“…Some studies demonstrated that, in cancer patients, higher levels of cfDNA are associated with higher risk of disease recurrence and progression [15, 28, 30, 66, 79–81]. In a study by Diehl et al .…”
Section: Clinical Application Of Cfdna In Cancer Managementmentioning
confidence: 99%
“…Some studies demonstrated that, in cancer patients, higher levels of cfDNA are associated with higher risk of disease recurrence and progression [15, 28, 30, 66, 79–81]. In a study by Diehl et al .…”
Section: Clinical Application Of Cfdna In Cancer Managementmentioning
confidence: 99%
“…The potential diagnostic, prognostic, and monitoring significance of plasma/serum cfDNA has been clearly demonstrated in breast cancer [6], lung cancer [7], ovarian cancer [8], prostate cancer [9] and gastric cancer [10]. In patients with RCC, Hauser's group demonstrates that levels of circulating cfDNA are increased and mostly originates from tumors [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of circulating cfNAs is influenced by the tumor size and the rate of their clearance [26][27][28]. As the quantifica tion of cfDNA concentrations overlap between healthy individuals and patients with benign and malignant disease [29,30], it is necessary to assess quantitative cfNAs in large cohorts of patients with well-defined clinical parameters. But the remaining high level of cfDNA of the same patient might indicate the presence of residual tumor cells or micro-metastasis in the tumor microenvironment [31].…”
Section: Circulating Nucleic Acids For Cancer Detection and Managementmentioning
confidence: 99%